Dome-Shaped Fountains - Matluba Moydinovna Khamrokulova (International Journal on Orange Technologies, 2021)
The article gives an overview of the design of a new dome figurative fountains and project scheme, with a brief introduction to the fountain landscape architecture from ancient to modern times.